Effective Export Strategy Issue for Foreign Trade Activity of the Develped Economy Enterprises - Oleg Tkach; Liubov Hryniv (Vasyl Stefanyk Precarpathian National University, 2023)
The published article presents possible ways penetration and promotion of goods into foreign markets based on experience of developed economies in the focus of separate business management decision. The purpose of the publishing is to identify the key features of overseas trade and business activity for developed, new organized companies and its strategies, managers, entrepreneurs and scientist. Within a way of decision making concern about foreign trade activity beginning is important to estimate all kind of business parts due to organize profitable business and minimize all the kind of risks. The publishing is analyzing the possibilities of the overseas trade activity for a Company regardless of a company business location and size. A significant expansion of the key features of overseas trade was noted. The authors present a special theoretical approaches and scientific solutions concern of decision-making regarding foreign economic activity within the framework of strategic planning and development of the enterprise regardless of its size and nature of the enterprise activity in the conditions of the development of global economic process. The scientific research of this publishing is based on the following methods: analyses, generalization to identify the key features of export and overseas business activity as well as to select structural characteristic for international trade activity that might be implemented to incoming companies' strategy of growing. The publication substantiates the need to control operating costs, acquire administrative and financial skills, and additional professional consulting services. There are main point for any managers like following: sense for exporting, obstacles to exporting, making the export decision, the pros and cons of exporting, getting the company ready to enter the export market, the new to export entrepreneur, key export products and destinations, the tools of trade, counseling sources. The presented article has practical significance in terms of minimizing possible management risks and can be useful for the successful start and development of foreign economic activity to any directions or type of the products and servicing.